REVITALISASI DAN AKTUALISASI HUKUM ADAT SEBAGAI SUMBER HUKUM PIDANA POSITIF - Sukirno, Sukirno (Fakultas Hukum, Universitas Diponegoro, 2018)
Article 2 of the Draft of the Criminal Code Law of 2015 provides a living law opportunity (adat law) in the community as the basis of criminal imposition or is also called the principle of material legality. However, the enactment of living law must be in accordance with the values of Pancasila, human rights and the principles of common law. In relation with the matter, there are three questions that need to be answered, i.e.: the legal expert's response to the addition of the living law in the Draft of the Criminal Code Law, living law requirements, preparation of regional governments to welcome the application of the principle of material legality. Living law is needed to overcome the gap between the acts derived from the living laws conceived by the community rather than the criminal. However, in the Criminal Code, it is conceived as a crime. Living law should be in accordance with Pancasila, human rights and the principles of common law. For this reason, adat law community needs to revitalize the laws, and, the regional governments should actualize the living laws with their regional regulations afterwards. Keywords: living law, the principle of material legality, revitalization, actualization